Transposon mutagenesis and genome sequencing identify two novel, tandem genes involved in the colony spreading of Flavobacterium collinsii, isolated from an ayu fish, Plecoglossus altivelis - Kondo, Yoshio; Ohara, Kenichi; Fujii, Ryoji; Nakai, Yudai; Sato, Chikara; Naito, Mariko; Tsukuba, Takayuki; Kadowaki, Tomoko; Sato, Keiko (Frontiers in Cellular and Infection Microbiology, 2023)
Bacteria of the family Flavobacteriaceae (flavobacteria) primarily comprise nonpathogenic bacteria that inhabit soil and water (both marine and freshwater). However, some bacterial species in the family, including Flavobacterium psychrophilum and Flavobacterium columnare, are known to be pathogenic to fish. Flavobacteria, including the abovementioned pathogenic bacteria, belong to the phylum Bacteroidota and possess two phylum-specific features, gliding motility and a protein secretion system, which are energized by a common motor complex. Herein, we focused on Flavobacterium collinsii (GiFuPREF103) isolated from a diseased fish (Plecoglossus altivelis). Genomic analysis of F. collinsii GiFuPREF103 revealed the presence of a type IX secretion system and additional genes associated with gliding motility and spreading. Using transposon mutagenesis, we isolated two mutants with altered colony morphology and colony spreading ability; these mutants had transposon insertions in pep25 and lbp26. The glycosylation material profiles revealed that these mutants lacked the high-molecular-weight glycosylated materials present in the wild-type strain. In addition, the wild-type strains exhibited fast cell population movement at the edge of the spreading colony, whereas reduced cell population behavior was observed in the pep25- and lbp26-mutant strains. In the aqueous environment, the surface layers of these mutant strains were more hydrophobic, and they formed biofilms with enhanced microcolony growth compared to those with the wild-type. In Flavobacterium johnsoniae, the Fjoh_0352 and Fjoh_0353 mutant strains were generated, which were based on the ortholog genes of pep25 and lbp26. In these F. johnsoniae mutants, as in F. collinsii GiFuPREF103, colonies with diminished spreading capacity were formed. Furthermore, cell population migration was observed at the edge of the colony in wild-type F. johnsoniae, whereas individual cells, and not cell populations, migrated in these mutant strains. The findings of the present study indicate that pep25 and lbp26 contribute to the colony spreading of F. collinsii.